Diare Kronis pada Anak Berusia di Bawah Lima Tahun - Grahana Ade Candra Wolayan; I Gusti Made Reza Gunadi Ranuh; Budiono Budiono; Alpha Fardah Athiyyah (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Diarrhea is an endemic disease in Indonesia and has the potential to cause outbreaks that are often accompanied by death, even the mortality rate during outbreaks in 2017, amounting to 1.97%, had not yet reached the expected target by the government, which is less than 1%. This study aims to determine the distribution of sex, age, nutritional status based on weight/age, and how to leave the hospital for chronic diarrhea patients and to know the correlation between nutritional status based on weight/age and death cases of chronic diarrhea in children under five years old treated at RSUD Dr. Soetomo in the period 2015-2019. This research was a retrospective analytical and descriptive study using secondary data from a patient's electronic medical record. Results showed that out of 45 chronic diarrhea patients, 28 (62,2%) were male, 16 (35,6%) children were in the 0 - 5 months age group, 18 (40,0%) children had good nutritional status, 39 (86,7%) children were discharged from the hospital, and there was a significant correlation between nutritional status based on weight/age and death cases of chronic diarrhea in children (p = 0,017). It could be concluded that the majority of children with chronic diarrhea were male, were in the 0 - 5 months age group, had good nutritional status, and were discharged from the hospital which meant that their condition had improved or cured and there was a significant correlation between nutritional status based on weight/age with death cases of chronic diarrhea in children.